2021
DOI: 10.11604/pamj.2021.40.194.31122
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of sexual interactions and associated factors among long-distance truck drivers operating along the Northern Corridor Highway, Kenya

Abstract: Introduction harsh working conditions among long-distance truck drivers (LDTDs) expose them to risky sexual interactions while on transit. As a result, the risky sexual interactions among the LDTDs place them at a high risk of contracting human immunodeficiency virus (HIV) and sexually transmitted infections (STIs). This study sought to assess the sexual interactions and associated factors among the LDTDs in Kenya. Methods two hundred ninety-six (296) LDTDs were intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The findings from this study demonstrate substantial evidence of high levels of HIV across LDTDs of diverse geographical backgrounds such as sub-Saharan Africa, Asia and the Pacific. While for a long time LDTDs were understood to be both most at-risk [5,6,9,13,15,17,19,80] and a hard-to-reach population [3,4,18,27], this is even the pioneer study to systematically determine and report the extent of the burden of HIV in this key population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from this study demonstrate substantial evidence of high levels of HIV across LDTDs of diverse geographical backgrounds such as sub-Saharan Africa, Asia and the Pacific. While for a long time LDTDs were understood to be both most at-risk [5,6,9,13,15,17,19,80] and a hard-to-reach population [3,4,18,27], this is even the pioneer study to systematically determine and report the extent of the burden of HIV in this key population.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have identified several factors likely to drive a high burden of HIV among LDTDs. These include; sexual risk behaviours like poor condom use [5][6][7][8], multiple sexual partners [9][10][11], illicit drug and alcohol use during or before sexual interactions [10,[12][13][14], and risky sexual networks [15][16][17][18]. Notably, LDTDs' stopovers along their transit routes are characterized by prevalent commercial sex from FSWs whose risk of HIV infection is also high [19].…”
Section: Introductionmentioning
confidence: 99%